2018
DOI: 10.2147/ott.s152818
|View full text |Cite
|
Sign up to set email alerts
|

RACK1 induces chemotherapy resistance in esophageal carcinoma by upregulating the PI3K/AKT pathway and Bcl-2 expression

Abstract: IntroductionAccumulating evidence indicates that RACK1 is involved in the progression of tumors. We aimed to evaluate the function of RACK1 in esophageal squamous cell carcinoma (ESCC) and its role in the mechanism of chemotherapy resistance.Materials and methodsTransfected ESCC cell lines with plasmids expressed shRACK1 or open reading frame (ORF) targeting RACK1 and established stable cell lines. We then examined the effects of RACK1 on cell proliferation and chemotherapy resistance in ESCC cell lines, and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 29 publications
(30 reference statements)
0
29
0
Order By: Relevance
“…Interestingly, recent studies have shown that Rack1 also confers resistance to cancer. Rack1 elevation enhances chemoresistance in leukemia, hepatocellular carcinoma, and esophageal cancer [39,41,43]; Rack1 overexpression promotes targeted therapy resistance in gastrointestinal stromal tumor [42]. These findings indicate that Rack1 might also be a critical hub involved in the crosstalk between drug resistance and invasion/metastasis.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Interestingly, recent studies have shown that Rack1 also confers resistance to cancer. Rack1 elevation enhances chemoresistance in leukemia, hepatocellular carcinoma, and esophageal cancer [39,41,43]; Rack1 overexpression promotes targeted therapy resistance in gastrointestinal stromal tumor [42]. These findings indicate that Rack1 might also be a critical hub involved in the crosstalk between drug resistance and invasion/metastasis.…”
Section: Discussionmentioning
confidence: 87%
“…In particular, higher Rack1 level is an independent predictor for poor prognosis in breast cancer. Recently, Rack1 has been reported to be a key protein involved in drug resistance in several carcinomas [39][40][41][42][43]. These findings have suggested that Rack1 may act as an important convergence point for drug resistance and invasion/metastasis.…”
Section: Introductionmentioning
confidence: 97%
“…PI3K translocates to the plasma membrane and subsequently phosphorylates AKT. As a key effector of PI3K, AKT also regulates various cellular responses, including cell proliferation and cell survival (41)(42)(43), and can sustain Bcl-2 expression in certain diseases (44,45). Previous studies have shown that v-3 FAs promoted the activation of ERK and PI3K/AKT pathways mainly via GPR120, exerting the antiapoptotic effect in certain cell lines (19,30,46,47).…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, the optimized concentration and treatment time of DDP for use in vitro were determined by MTT assay; 1.5x10 -5 M DDP treatment for 24 h was selected for further investigation. The optimized concentration (1.5x10 -5 M) in the study is similar to the clinically used dose of DDP (20 mg/m 2 /day) (38,39). The effect of CtBP2 on the cell apoptosis induced by DDP was investigated by Hoechst 33342 staining and FCM.…”
Section: Discussionmentioning
confidence: 99%